Metodologi Pemahaman Hadis Abad XXI: Tradisi dan Inovasi dalam Studi Hadis Kawasan - Wagola, Zulkifli (Journal of Hadith Studies, 2022)
The transmission of hadith understanding in Indonesia is often perceived as rigid and authoritative. However, beneath this perception lies a complex methodological dynamic. The interplay between religious authority, local traditions, and global thought provides a space for critical engagement. This study aims to identify and analyze the methodological approaches applied in hadith studies in 21st-century Indonesia and propose future directions for methodological development. Two key issues are addressed: first, how contextual approaches are applied in the methodology of hadith interpretation by Indonesian scholars in the 21st century; and second, what criteria are employed by hadith experts in evaluating narrations within a modern context. This research adopts a qualitative approach through a library-based study. Data analysis includes literature review, textual analysis of hadith and relevant scholarly works, interpretation within socio-historical contexts, and formulation of conclusions and recommendations based on the findings. The study reveals that early scholars such as al-Raniri and al-Maqassari, along with modern figures like Muhammad Syuhudi Ismail, Kamaruddin Amin, and Tengku Muhammad Hasbi Ash-Shiddieqy, highlight the significance of flexibility and critical analysis in hadith comprehension. Moreover, scholars such as Ali Mustafa Ya’qub and Kamaruddin Amin emphasize the synergy between tradition and innovation, which fosters a more inclusive understanding of hadith in the Indonesian context. The findings of this research are expected to enrich the academic discourse in hadith studies by illustrating how contextual approaches and modern criteria for hadith criticism can be adapted to address contemporary challenges.